LOGO SHELL BENTUK KERANG YANG MUDAH DIKENANG - Susilo Tri Hartanto (Institut Seni Indonesia Yogyakarta, 2012)
According to AI Surveillance Ries and Laura Surveillance Ries brand is a word in the mindconsumers, a word, which is called a proper noun, where the words objects that show people, place, and,etc. this has the power to influence on it, so every proper noun is essentially a brand and can likes whatevername, so that nobody is a brand? In addition will be easier for consumers to recognize and buy goodswhich gave her satisfaction, can also be able to differentiate company or individual that one to another intheproductthattheyo.ffer(Jejkins, 1997: 296).Use company identity in a product, making consumers to quickly identifY, to remember, causing agreat impression or the image even to all the things associated with it. Especially when identity is createdthrough a unique design or a special be realized through unity elements color, shape, and the letter.Keywords: Logo, mimesis, remainder